Analysis of Arrests in Paris, June 1848 - Tilly, Charles ([Verlag nicht ermittelbar], 1984)
This data collection contains three files pertaining to the June 1848 insurrection in Paris and to people charged with or arrested for participation in the insurrection. The data files contain social, economic, and demographic information. Information is provided on the results of the judicial proceedings against the individual after arrest, as well as demographic characteristics of the individual, such as occupation, place of birth, sex, age, marital status, number of children, and place of residence (Part 1), the number of inhabitants arrested in connection with the rebellion, the labor force, and social characteristics of the 12 zones (arrondisements) (Part 2), and demographic and arrest information with a focus on the furnished apartments, clubs, and popular societies within the 48 quartiers (districts) existing in Paris in 1848 (Part 3).